Fenomena Kotak Kosong Dalam Pilkada Tahun 2024 - Mulyadi, Dedi; Simbolon, Cindy Claudia; Baidhowi, Nayla Ratu; Januwati, Pusfa; Lananda, Ardelia; Rahmah, Mila Arastasya (Jurnal Hukum Ius Publicum, 2024)
The implementation of regional head elections (Pilkada) in Indonesia faces various challenges, including the phenomenon of empty boxes that reflect public dissatisfaction with the candidates nominated. In the context of democracy, Pilkada should be a means for the people to express their sovereignty. However, the issue of the threshold and the practice of "party buying" hinder healthy political participation. The approach method in this study is to use a normative legal approach, namely a legal research method that examines library materials or secondary data. The identification of problems in this study is the Background of the Initial Phenomenon of Empty Boxes, Problems or Implementation of Pilkada Against Empty Boxes in Several Regions in Indonesia, and how Efforts to Resolve Pilkada Against Empty Boxes. The purpose of this study is to analyze in more depth the phenomenon of empty boxes in the 2024 Pilkada in the perspective of the Constitutional Court Decision No. 60 / PUU-XXII / 2024, as well as to add insight and information regarding the phenomenon of empty boxes in the 2024 Pilkada in the perspective of the Constitutional Court Decision No. 60 / PUU-XXII / 2024. The results of the study show that although the Constitutional Court's decision provides space for candidates without a threshold, challenges remain in terms of candidate quality and public acceptance. Internal party cadre formation is a strategic step to produce leaders who are more representative and able to answer the aspirations of the people. This study suggests the need for reform in the electoral system to improve the quality of democracy in Indonesia.